Kajian Yuridis Multidimensi: Mengatasi Tantangan Eksploitasi Anak dan Mengembangkan Solusi Hukum Adaptif - Muh. Farhan Mushsinulkhair FR; Muhammad Sabir Rahman; Patahillah Asba; Muhammad Darwis (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
The results of the study showed that the factors that led to the exploitation of children in Parepare City were economic, low education from parents, and lack of education related to exploitation issues, which caused parents not to know that if a minor was employed it would already be included in the realm of a crime even though it was their child, and another factor was the general public's lack of awareness in reporting child exploitation. 35 of 2014 concerning Child Protection which reads